Woolly Mammoth in Trouble - Bently, Dawn; Carr, Karen; Galvin, Laura Gates; Pilchowski, Marcin D (Washinton, USA Soundprints, 2003)
Wooly Mammoth is at home on the cold plains of Europe. As a storm comes and heavy snow falls, Wooly Mammoth realizes he is lost. A pack of saber-tooth tigers catches sight of Wooly Mammoth. Can he find his way out of trouble? Kids are bound to love this book with its detailed illustrations and storyline that has been reviewed by paleontologists at the Smithsonian Institution for accuracy. Watch your child join Stegosaurus on a prehistoric adventure in this thrilling story
Available First Edition in 2004 at Misr Public Library - Mobile Library
Includes a tear - out poster!
Science (Animals)
Keywords: Animals